2007
DOI: 10.1158/1055-9965.epi-07-0041
|View full text |Cite
|
Sign up to set email alerts
|

Allergy-Related Polymorphisms Influence Glioma Status and Serum IgE Levels

Abstract: Previous studies have shown that glioma patients report allergies less frequently than controls, harbor lower atopyassociated IgE levels, and harbor different frequencies of polymorphisms in the IL13 and IL4 pathways than controls. We sought to confirm this latter result and extend the analysis to IgE levels. Glioma patients (n = 456) and controls (n = 541) were genotyped for genetic variants in IL4, IL4R, and IL13 and tested for total IgE levels (n = 248 controls and 289 cases). Among Whites, IL4 and IL4R pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 25 publications
(31 reference statements)
0
51
1
Order By: Relevance
“…Schwartzbaum et al found that genetic variants that increase the risk of IgE or allergies also decrease glioblastoma risk. Their finding for the IL-13, rs1800925 SNP was confirmed for glioma by Wiemels et al (20) in a large case-control study of glioma (456 cases, 541 controls). Furthermore, Wiemels et al report that the same IL-13 SNP was inversely associated with IgE levels among controls (P = 0.04) as was the IL-13 rs20541 SNP (P < 0.001).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Schwartzbaum et al found that genetic variants that increase the risk of IgE or allergies also decrease glioblastoma risk. Their finding for the IL-13, rs1800925 SNP was confirmed for glioma by Wiemels et al (20) in a large case-control study of glioma (456 cases, 541 controls). Furthermore, Wiemels et al report that the same IL-13 SNP was inversely associated with IgE levels among controls (P = 0.04) as was the IL-13 rs20541 SNP (P < 0.001).…”
Section: Introductionmentioning
confidence: 69%
“…In their large case-control study of glioma, Wiemels et al (20) also found suggestive evidence for an association of borderline statistical significance between an IL-4Ra haplotype and glioma (OR, 1.49; 95% CI, 0.99-2.25). However, their haplotype includes four SNPs in addition to the two that we evaluated.…”
Section: Discussionmentioning
confidence: 94%
“…Subject recruitment has been detailed previously (6,7). Briefly, eligible case subjects included incident adult (age >20 y) glioma cases diagnosed between August 1991 and April 1994 (series 1) and between May 1997 and August 1999 (series 2), who resided in six San Francisco Bay Area counties at the time of diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Within each pathway, RF analyses were done with SNPs using randomForest R package version 4.5-18 (by Liaw and Wiener), available through the Comprehensive R Archive Network (CRAN) website. 6 Of the 227 SNPs examined in this analysis (33 SNPs belong to more than one pathway), 149 SNPs had some missing values. Among these 149 SNPs, 134 (90%) had <5% with missing values.…”
Section: Statistical and Bioinformatic Methodsmentioning
confidence: 99%
“…A pooled analysis of nine population-based studies failed to establish NOCs as a causal agent for glioma. 85 PBTs molecular epidemiologic studies with focus on inflammation An inverse association between IL-4RA, IL-13, and glioblastoma was observed and the relationship was not affected by allergic conditions (Table 4 [86][87][88][89][90][91][92] ). The studies also provide evidence to establish allergies as a risk factor for glioma and thus urge the identification of more candidate genes to be studied under this category.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Metabolismmentioning
confidence: 99%